2021
DOI: 10.1021/acs.est.0c07274
|View full text |Cite
|
Sign up to set email alerts
|

Peroxydisulfate Activation and Singlet Oxygen Generation by Oxygen Vacancy for Degradation of Contaminants

Abstract: Oxygen vacancies (OVs) play a crucial role in the catalytic activity of metal-based catalysts; however, their activation mechanism toward peroxydisulfate (PDS) still lacks reasonable explanation. In this study, by taking bismuth bromide (BiOBr) as an example, we report an OV-mediated PDS activation process for degradation of bisphenol A (BPA) employing singlet oxygen (1O2) as the main reactive species under alkaline conditions. The experimental results show that the removal efficiency of BPA is proportional to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 330 publications
(101 citation statements)
references
References 87 publications
5
95
1
Order By: Relevance
“…After the reaction proceeds to 60 min, BPA and resorcinol are almost degraded, different from the degradation of BA (∼58%), which is a typical probe for SO 4 •– . The selective degradation of organics, as well as less contribution of SO 4 •– , suggests that it might be a nonradical-dominant oxidation process . In addition, the TOC removal efficiencies (Figure S11a) are ∼49, ∼37, ∼36, ∼30, ∼25, and ∼19% for BPA, resorcinol, phenol, 4-CP, p -nitrophenol, and BA within 60 min, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…After the reaction proceeds to 60 min, BPA and resorcinol are almost degraded, different from the degradation of BA (∼58%), which is a typical probe for SO 4 •– . The selective degradation of organics, as well as less contribution of SO 4 •– , suggests that it might be a nonradical-dominant oxidation process . In addition, the TOC removal efficiencies (Figure S11a) are ∼49, ∼37, ∼36, ∼30, ∼25, and ∼19% for BPA, resorcinol, phenol, 4-CP, p -nitrophenol, and BA within 60 min, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…Our previous study discovered that ND bearing carbonyl groups could activate PMS to produce 1 O 2 for 4-chlorophenol (4-CP) removal. The proposed 1 O 2 -dominated oxidation was validated by chemical quenching, electron paramagnetic resonance (EPR) studies, and 1 O 2 probing experiments. Furthermore, the critical role of singlet oxygenation in persulfate systems was also reported in the recent literature. ,, For example, Zhou et al reported that benzoquinone (BQ) activated PMS to generate 1 O 2 for the elimination of sulfamethoxazole. Bu et al showed that oxygen vacancy-rich bismuth bromide promoted persulfate decomposition to produce 1 O 2 , which was responsible for bisphenol A degradation.…”
Section: Introductionmentioning
confidence: 77%
“…The proposed 1 O 2 -dominated oxidation was validated by chemical quenching, electron paramagnetic resonance (EPR) studies, and 1 O 2 probing experiments. Furthermore, the critical role of singlet oxygenation in persulfate systems was also reported in the recent literature. ,, For example, Zhou et al reported that benzoquinone (BQ) activated PMS to generate 1 O 2 for the elimination of sulfamethoxazole. Bu et al showed that oxygen vacancy-rich bismuth bromide promoted persulfate decomposition to produce 1 O 2 , which was responsible for bisphenol A degradation. In addition, Yin and Gao also proposed that singlet oxygenation was of paramount importance to degrading OMPs in nanocarbon/persulfate systems.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The SiNCs absorbed near-UV radiation and then transferred this energy to the triplet state of the attached dyes, which increased the number of triplet states and finally enhanced the singlet oxygen generation (Beri et al, 2020). As a reactive oxidant, singlet oxygen exhibited great potential for quantities of applications, such as chemical synthesis (Manfrin et al, 2019;Karsili andMarchetti, 2020), environmental protection (García-Fresnadillo, 2018;Bu et al, 2021), and photodynamic therapy (Guo et al, 2010; Bartusik-Aebisher Osuchowski et al, 2021), and thus the application fields of SiNCs were also broadened. Photonic devices have always been another sought-after field for SiNCs with high QY value and solution processibility after functionalization.…”
Section: Other Applicationsmentioning
confidence: 99%